(untitled) (Scientific journal of the Fergana State University, 2024)
The article highlights the problem of Tunkat, which was the capital of Ilak in the Middle Ages, reflected in written and archaeological sources. It is known that as a result of research, the localization and topography of the city of Tunkat-Imlok have been discussed for a long time. In particular, the description of Tunkat in written sources has not been confirmed in archaeological materials. The article summarizes new information on this matter and provides some comments.